Comprehensive Overview of Innovative Strategies in Preventing Renal Ischemia-reperfusion Injury: Insights from Bibliometric and In silico Analyses - Rysmakhanov, Myltykbay S.; Zare, Afshin; Smagulov, Aibolat S.; Abenova, Nurgul A.; Mussin, Nadiar M.; Sultangereyev, Yerlan B.; Zhakiyev, Bazylbek S.; Kuttymuratov, Gani K.; Haberal, Mehmet; Jafari, Nazanin; Baneshi, Hanieh; Bakhshalizadeh, Shabnam; et al. (Current Pharmaceutical Design, 2024)
Background: Ischemia-reperfusion Injury (IRI) is a complex pathophysiological process with severe consequences, including irreversible loss of renal function. Various intraoperative prevention methods have been proposed to mitigate the harmful effects of warm ischemia and kidney reperfusion. Aim: This comprehensive analysis provides an overview of pharmacological agents and intraoperative methods for preventing and treating renal IRI. Methods: Our analysis revealed that eplerenone exhibited the highest binding affinity to crucial targets, including Aldehyde Dehydrogenase (AD), Estrogen Receptor (ER), Klotho protein, Mineralocorticoid Receptor (MR), and Toll-like Receptor 4 (TLR4). This finding indicates eplerenone's potential as a potent preventive agent against IRI, surpassing other available therapeutics like Benzodioxole, Hydrocortisone, Indoles, Nicotinamide adenine dinucleotide, and Niacinamide. In preventing kidney IRI, our comprehensive analysis emphasizes the significance of eplerenone due to its strong binding affinity to key targets involved in the pathogenesis of IRI. Results: This finding positions eplerenone as a promising candidate for further clinical investigation and consideration for future clinical practice. Conclusion: The insights provided in this analysis will assist clinicians and researchers in selecting effective preventive approaches for renal IRI in surgical settings, potentially improving patient outcomes.
Keywords: renal resection